2020
DOI: 10.1155/2020/8869201
|View full text |Cite
|
Sign up to set email alerts
|

Functional Correlates of Action Observation of Gait in Patients with Parkinson’s Disease

Abstract: Background. Action observation (AO) relies on the mirror neuron system (MNS) and has been proposed as a rehabilitation tool in Parkinson’s disease (PD), in particular for gait disorder such as freezing of gait (FOG). In this study, we aimed to explore the brain functional correlates of the observation of human gait in PD patients with (FOG+) and without (FOG-) FOG and to investigate a possible relationship between AO-induced brain activation and gait performance. Methods. Fifty-four participants were enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…In particular, the activity of bilateral SMA and right frontal and right superior temporal lobules in PD NOFOG decreased compared with normal controls during normal gait MI. These findings are consistent with the results of an action observation fMRI study of normal walking in PD (Bommarito et al, 2020 ). From the physiological point of view, the SMA and premotor cortex have a tight connection to the spinal cord and brainstem reticular formation, including the pedunculopontine nucleus (PPN) area and MLR (Aravamuthan et al, 2009 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In particular, the activity of bilateral SMA and right frontal and right superior temporal lobules in PD NOFOG decreased compared with normal controls during normal gait MI. These findings are consistent with the results of an action observation fMRI study of normal walking in PD (Bommarito et al, 2020 ). From the physiological point of view, the SMA and premotor cortex have a tight connection to the spinal cord and brainstem reticular formation, including the pedunculopontine nucleus (PPN) area and MLR (Aravamuthan et al, 2009 ).…”
Section: Discussionsupporting
confidence: 92%
“…It could not simply be explained by a single gait parameter or the activity in one single brain region. A recent study illustrated that gait variability of stride length and walking velocity positively correlated with precuneus neural activity in PD FOG (Bommarito et al, 2020 ). The finding charged a new possibility for exploiting the relationship among the sophisticated FOG brain activities and gait parameters in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these oscillations have shown sensitivity both to action observation and EBL. In particular, the mu rhythm – a well‐known oscillation in the alpha band (i.e., 8–13 Hz) recorded over central sensors – shows a consistent ERD during action execution and observation (Bommarito et al, 2020; Debnath et al, 2019; Oberman et al, 2005; Pineda, 2005). This activity reflects motor resonance, i.e., the mapping of observed motor actions onto one's motor representations – a phenomenon occurring later than the early freezing response to EBL (Borgomaneri et al, 2015a; Spaccasassi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The observation of action seems to involve the generation of the internal representation of that same action in the observer, a process named Motor Resonance (MR) 1 , 2 . Importantly, action observation determines the activation of different networks located in the visual, motor, and perceptive areas 3 .…”
Section: Introductionmentioning
confidence: 99%
“…People with Parkinson's disease appear to have a slowdown in the form of motor learning, probably due to impairment in executive functions 6 . Recent neuroimaging studies reported a defect in brain areas during observation of gait in Parkinson’s disease patients 3 . The basal dysfunction of PD may play a role in the functioning of motor resonance mechanisms.…”
Section: Introductionmentioning
confidence: 99%